On elastic energy of structures under proportional loading - Gawęcki, A. (Archives of Mechanics, 1998)
The paper concerns the proportional loading of structures made of time independent materials. It has been shown that the elastic energy can be a decreasing function of the load multiplier if unilateral constraints are introduced into an elastic-plastic structure. Results obtained in the work seem to be of importance for the theory of structures and may have some theoretical implications. An exhaustive example illustrates the theory.